2009
DOI: 10.2967/jnumed.109.065300
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET as a Routine Posttreatment Surveillance Tool in Oral and Oropharyngeal Squamous Cell Carcinoma: A ProspectiveStudy

Abstract: The purpose of this study was to evaluate the role and timing of serial 18 F-FDG PET scans as routine surveillance for detecting early locoregional recurrence, distant metastases, and second primary tumors in patients treated for advanced squamous cell carcinoma (SCC) in the oral cavity or oropharynx during the first year after completion of their curative treatment. Methods: Forty-eight consecutive patients with SCC in the oral cavity or oropharynx were included after completing their initial therapy with cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 34 publications
4
58
0
1
Order By: Relevance
“…Multiple prior studies have also found the relative unreliability of an elevated SUV in differentiating recurrent tumor from ORN. 11,12,[16][17][18] While recurrent tumor does, in general, demonstrate higher SUV mean and SUV max values compared with ORN, there is significant overlap, which makes differentiating the 2 entities on a case-by-case basis extremely unreliable. This overlap is presumably responsible for previous reports of false-positive results in PET scans attributed to osteoradionecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prior studies have also found the relative unreliability of an elevated SUV in differentiating recurrent tumor from ORN. 11,12,[16][17][18] While recurrent tumor does, in general, demonstrate higher SUV mean and SUV max values compared with ORN, there is significant overlap, which makes differentiating the 2 entities on a case-by-case basis extremely unreliable. This overlap is presumably responsible for previous reports of false-positive results in PET scans attributed to osteoradionecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent article by Krabbe et al (1), in which the authors prospectively evaluated the impact and timing of 18 F-FDG PET for posttreatment surveillance of oral and oropharyngeal squamous cell cancer. Forty-eight patients were included after completing their initial therapy with curative intent.…”
Section: To the Editormentioning
confidence: 99%
“…Another option for improving response evaluation might be to repeat PET scans during follow-up. Although in the study by Sjövall et al [17] this seemed not to improve the response evaluation, in the study by Krabbe et al [19] the detection of residual neck disease improved. Preliminary data [20] have indicated that a combination of 18 F-FDG PET and DW-MRI may be an attractive option for optimizing the decision making to perform a neck dissection following chemoradiotherapy.…”
mentioning
confidence: 94%
“…Marcus et al [18] recently proposed the five-point BHopkins scale^based on intensity (similar to the Deauville scale, but using the jugular vein rather than the mediastinal blood pool), adding a description of aspects of residual uptake (focal or diffuse). Krabbe et al [19] graded the confidence of image interpretation using a five-point scale (0 definitely no tumour, 1 probably no tumour, 2 equivocal, 3 probably tumour, and 4 definite tumour). Schouten et al [20] used a similar system based on aspect and intensity.…”
mentioning
confidence: 99%